Virtual place navigator: Enhancing architectural education through immersive virtual reality for experiential learning on the sense of place / Izham Ghani ... [et al.] - Ghani, Izham; Abdul Rahman, Norhafizah; Teh, Mohd Zulhaili; Abdullah, Marina; Borhan, Ruwaidah (2024)
Integrating advanced technologies into architectural education can profoundly transform learning experiences, particularly through Virtual Reality (VR). The ‘Virtual Place Navigator’ project leverages VR to create immersive virtual environments (VEs) that enhance students’ experiential learning and understanding of the sense of place in architectural studies. This project adopts a qualitative approach, utilising in-depth semi-structured interviews and the ‘think aloud’ method during VR sessions enriched with gamification elements. This project identifies four crucial components of virtual place: settings, activities, meanings, and immersion that could effectively ‘transport’ users to alternate locations and experiences. These components collectively facilitate a deeper understanding of spatial relationships and design principles. The findings demonstrate that specific criteria must be met before representing contents within a VE to establish a genuine sense of place in architectural virtual environments. By simulating real-world spatial experiences, VR provides a dynamic and interactive platform for architectural education, bridging the gap between theoretical knowledge and practical application. This project lays the groundwork for integrating VR into architectural pedagogies, highlighting its potential to revolutionise the learning process and prepare students for the demands of contemporary architectural practice.